Kesiapan Desa dalam Implementasi Undang-Undang No 6 Tahun 2014 tentang Desa (Studi Pengelolaan Anggaran Dana Desa di Desa Kalisidi Kecamatan Ungaran Barat Kabupaten Semarang) - Ardang, Rifvan Yuniar; Lestari, Puji; Sunarto, Sunarto (Universitas Negeri Semarang, 2018)
In this sresearch conducted in Kalisidi Village, Sub-District West Ungaran, Semarang Regency. The purpose of this research is to determine (1) the Readiness of the village administration in the management of the estimate fund village management village as the implementation of Law No. 6 of 2014 about village. (2) To find programs or activities to take advantage of the estimate fund village in the Kalisidi village area, Sub- District West Ungaran, Semarang Regency. (3) To determine the involvement of the villagers in the management and use of fund village in Kalisidi Village, Sub-District West Ungaran, Semarang Regency. This study used a qualitative method. Sources of data obtained from informants and documents. Data captured through interviews, observation and documentation. The results showed that before implementing the management of the estimate fund village, the village government can technical guidance (bintek) from the central government, provincial government and district government, so in implementing of the estimate fund village, village government can carry out identification of problems, setting priorities and socialization in determining the village programs.